Hypothalamic GABAergic neurons: their roles in health and metabolic diseases - Wang, Bingwei; Yu, Yang; Li, Juan; Xiong, Yu; Zhang, Xin; Wan, Ying; Zheng, Ruimao; Zhang, Chunxiang (Frontiers in Endocrinology, 2025)
Hypothalamic GABAergic neurons are important in regulating metabolic homeostasis and energy balance. Serving as critical integrators of catabolic and anabolic processes, these neurons orchestrate a broad spectrum of metabolic functions, including feeding, nutrient metabolism, fluid homeostasis, basal metabolism, thermoregulation, and circadian rhythms. Recent advances in neuroscience have facilitated a deeper exploration of the role of hypothalamic GABAergic neurons in metabolic regulation. Emerging research has uncovered key mechanisms through which these neurons modulate energy balance and maintain metabolic balance. These findings not only enhance our understanding of obesity and related metabolic disorders but also underscore the link between hypothalamic dysfunction and prevalent metabolic diseases such as obesity and type 2 diabetes. This review summarizes the latest advancements in our understanding of the role of hypothalamic GABAergic neurons in metabolic regulation. It aims to elucidate the neural and molecular mechanisms underlying hypothalamic control of metabolism, offering new perspectives for the diagnosis and treatment of metabolic disorders.